OP0049 Aberrant vista expression on cd45ra+cd25dim th-cells in giant cell arteritis. (12th June 2018) - Hid Cadena, R.; Reitsema, R.D.; Abdulahad, W.H.; Huitema, M.G.; Boots, A.M.; Heeringa, P.; Brouwer, E.
Abstract : Background: A broad naïve Th-cell repertoire is needed to face novel antigenic challenges and mounting an optimal immune response. 1 2 The replenishment of naïve T-cells is severely restricted by thymic involution with ageing. 3 In the past, our group provided new insight into the homeostasis of human Th-cells, identifying CD45RA + CD25 dim Th-cells as a subset of post-thymically expanded naïve Th-cells in healthy aged individuals. 4 Immune homeostasis of naïve Th-cells is especially important to understand defective immune responses in age-related immune disorders such as Giant Cell Arteritis (GCA). Recently, a loss of immunoinhibitory checkpoints has been implicated in GCA. 5 6 The possible contribution of immune checkpoint pathways to the dysregulation of Th-cells, especially in CD45RA + CD25 dim Th-cells in GCA has not yet been studied. Objectives: In this study, we aimed to investigate the expression of different immune checkpoint molecules on circulating CD45RA + CD25 dim Th-cells of GCA-patients and compare it with matched healthy controls (HCs). Methods: In a cross-sectional study, fresh blood samples were obtained from 33 GCA-patients with/without immunosuppressive treatment (glucocorticoids) and 12 sex/age-matched HCs. The frequency of the expression of different immune checkpoints including CD28, Cytotoxic T-Lymphocyte-associated antigen-4 (CTLA-4), Programmed death- 1 (PD-1), and V-domain Ig suppressor of T cell activation (VISTA) were determined on CD45RA + CD25 dim Th-cells of GCA-patients and HCs by flow cytometry. Results: Proportion of circulating CD45RA + CD25 dim Th-cells in GCA-patients was not different when compared to HCs, whereas significant increase in these cells was observed only in treated GCA-patients when compared to HCs. The proportion of CD28, CTLA-4 and PD-1 expression on CD45RA + CD25 dim Th-cells did not differed between GCA-patients and HCs. Interestingly, proportion of VISTA expression on these cells was significant decreased in GCA-patients. Furthermore, decreased frequency of VISTA expression was seen in both untreated and treated patients. Conclusions: In GCA-patients(untreated and treated), lower frequencies of VISTA + CD45RA + CD25 dim Th-cells were noted. Decreased VISTA expression in GCA-patients could play a role in the regulation of Th-cell activation/inhibition. The functional consequences of immune checkpoint modulation within particular subsets requires further investigation. References: [1] Nikolich-Žugich J, Slifka MK, Messaoudi I. The many important facets of T-cell repertoire diversity. Nat. Rev. Immunol2004;4:123–132. [2] Goronzy JJ, Lee WW, Weyand CM. Aging and T-cell diversity. Experimental Gerontology2007;42:400–406. [3] den Braber I, et al. Maintenance of peripheral naive t cells is sustained by thymus output in mice but not humans. Immunity2012;36:288–297. [4] van der Geest KSM, et al. Low-affinity TCR engagement drives IL-2-dependent post-thymic maintenance of naive CD4+ T cells in aged humans. Aging Cell2015;14:744–753. [5] Zhang H, et al. Immunoinhibitory checkpoint deficiency in medium and large vessel vasculitis. Proc. Natl. Acad. Sci 2017;114(6):E970–E979. doi:10.1073/pnas.1616848114 [6] Onuora S. Vasculitis syndromes: Loss of immunoinhibitory checkpoint implicated in GCA. Nat. Rev. Rheumatol2017;13:129–129. Disclosure of Interest: None declared